The technosignature researcher on the lookout for exo-civilizations. (1st February 2022) - Appell, David
Abstract : Meet Sofia Sheikh, one of a handful of postdoctoral researchers who have specialized in the search for extraterrestrial intelligence. She talks to David Appell about strange signals, Star Trek, picking a tricky research field and the importance of mentorship.